(untitled) (Semiárida, 2020)
Daily weight gains of barrow and gilts from 40 to 100 Kg live weight, were compared under a similar feeding treatment. Three groups of eight pigs each were allocated in two boxes. Forty-eight crossed and backcrossed Duroc Jersey x Hampshire pigs were used. Barrows showed significant greater daily gains in relation to the mixed group (0,948, 0,867 and 0,852 Kg/day respective ly). When gilts and mixed groups were compared, gilts showed a better performance but differences were not significant (P:0,05). Greater differences of daily gain of barrows were obtained during the finishing period (1,000,0,869 and 0,849 Kg/day respectively). Sailing prices at the Mercado Nacional de Haciendas showed no differences between groups.